1998
DOI: 10.1038/sj.onc.1201941
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the c-Jun N-terminal kinase (JNK) signaling pathway by curcumin

Abstract: Curcumin, a dietary pigment in curry, suppresses tumor initiation and tumor promotion. Curcumin is also a potent inhibitor for AP-1 and NF-kB activation. In this report, we show that curcumin inhibits JNK activation by various agonists including PMA plus ionomycin, anisomycin, UV-C, g radiation, TNF-a, and sodium orthovanadate. Although both JNK and ERK activation by phorbol 12-myristate 13-acetate (PMA) plus ionomycin were suppressed by curcumin, the JNK pathway was more sensitive. The IC 50 (50% inhibition c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
178
1
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 363 publications
(193 citation statements)
references
References 39 publications
11
178
1
3
Order By: Relevance
“…The activation of JNK was chemically inhibited by curcumin. Curcumin 20 mm was the lowest concentration that inhibited JNK activation at 24 h, in agreement with prior studies (Chen and Tan, 1998). At this concentration, curcumin also diminished the cleavage of PARP to background levels ( Figure 2a).…”
Section: Taxotere-induced Parp Cleavage Is Mediated Through Jnk Activsupporting
confidence: 79%
See 1 more Smart Citation
“…The activation of JNK was chemically inhibited by curcumin. Curcumin 20 mm was the lowest concentration that inhibited JNK activation at 24 h, in agreement with prior studies (Chen and Tan, 1998). At this concentration, curcumin also diminished the cleavage of PARP to background levels ( Figure 2a).…”
Section: Taxotere-induced Parp Cleavage Is Mediated Through Jnk Activsupporting
confidence: 79%
“…Blocking JNK activation with a variety of inhibitors reversed Taxotere-induced PARP cleavage. While inhibitors such as curcumin (diferuloylmethane) can inhibit c-Jun and NF-kB, JNK and ERK, the dose that inhibited JNK did not inhibit p38 or ERK, as demonstrated here or previously (Chen and Tan, 1998). The other inhibitors also acted specifically on JNK.…”
Section: Discussionmentioning
confidence: 67%
“…Others and we have previously demonstrated that curcumin effectively inhibits the extracellular signalregulated kinase (ERK) in a variety of cells, including colon cancer cells (Chen and Tan, 1998;Chen et al, 1999;Jobin et al, 1999). To determine the role of the ERK signal pathway in curcumin inhibition of the egfr promoter activity, Moser cells were cotransfected with the plasmid pER1-Luc and the cDNA expression plasmid pdn-ERK, or pa-ERK, at indicated doses.…”
Section: Curcumin Inhibits Gene Expression Of Egfr In Human Colon Canmentioning
confidence: 99%
“…The constructs for Flag-PP4 (PPX), GST-Jun(1 ± 79), and Flag-MKK7 were described previously (Chen and Tan, 1998;Hu et al, 1998;Yao et al, 1997).…”
Section: Plasmidsmentioning
confidence: 99%